SINDIUTE e a defesa da educação pública: a importância da luta sindical no avanço de uma educação da classe trabalhadora para a classe trabalhadora - Santos, Juliana Kecia de Menezes (2024)
The current configuration of Brazil's public education system has characteristics that, in addition to being flawed, denote projects aimed at nullifying any success for public school students. This topic was chosen based on experiences in the classroom and in the activities of the Fortaleza Education Workers' Union (Sindiute). The central aim of this research is to analyze the concept of education defined by Sindiute's management team. In order to do so, we will analyze how the education workers' union (Sindiute) acted in the process of changes that national education went through between 2016 and 2022, as well as demarcating which actions and/or political positions were adopted in affirming this conception of education. We will therefore carry out a theoretical and documentary (hemerographic) investigation of Sindiute's actions and position in the process of building proposals for quality public education geared towards the interests of the working class. We start from the hypothesis that an institution organized by education workers must ensure that education is based both on the principles of public, secular and free education that have already been achieved and on the principles of education that promotes the right of students who are children of the working class to access quality public education.